An online behavior change intervention to promote physical activity in adults with asthma: study protocol for a multicenter randomized controlled trial - de Oliveira J.M. (2022)
© 2022, The Author(s).Background: Behavior change interventions have been the focus of recent studies, and the COVID-19 pandemic highlighted the importance of online interventions. However, no previous studies have investigated behavior change techniques to improve physical activity in adults with asthma through online intervention. Methods: This double-blind clinical trial will investigate the effectiveness of an online behavior change intervention in increasing physical activity and reducing sedentary behavior in adults with asthma, as well as in improving other clinical outcomes in short and medium terms. Patients with clinically stable moderate to severe asthma, who are physically inactive and do not have cardiovascular and/or osteoneuromuscular impairments will be randomized into control or intervention groups (23 in each). Both groups will carry out an online educational program (1 h). Additionally, the intervention group will receive weekly individual online sessions for 12 weeks of motivation-based behavior change intervention to promote an increase in physical activity and reduce sedentary behavior based on both self-determination theory and transtheoretical model. The intervention group will also receive an activity monitor with specific strategies related to it. Both groups will be reassessed immediately after the intervention and 6 months after that. The primary outcomes are physical activity and sedentary behavior, which will be objectively assessed by a triaxial accelerometer (Actigraph wGT3X-BT). Secondary outcomes are Asthma Control Questionnaire, Incremental Step Test, Sit-To-Stand, Timed Up-and-Go, 4-Metre Gait Speed, Asthma Quality of Life Questionnaire, Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale, Actiwatch 2, and the Hospital Anxiety and Depression Scale. Discussion: The intervention is unprecedented and was carefully developed to joint most characteristics and techniques of both behavioral strategies (transtheoretical model and self-determination theory). Therefore, this intervention has the potential to improve physical activity levels and asthma management and reduce sedentary behavior. As a consequence, this novel intervention will improve global health in this population and support its use in clinical practice. The intervention will be carried out online with direct weekly contact with the therapist. Consequently, it has low implementation costs, might improve patient’s attendance, and has the potential to be largely offered elsewhere. Trial registration: ClinicalTrials.govNCT05241223. Registered on January 22, 2022.